Triptolide Upregulates Myocardial Forkhead Helix Transcription Factor p3 Expression and Attenuates Cardiac Hypertrophy - Ding, Yuan-Yuan; Li, Jing-Mei; Guo, Feng-Jie; Liu, Ya; Tong, Yang-Fei; Pan, Xi-Chun; Lu, Xiao-Lan; Ye, Wen; Chen, Xiao-Hong; Zhang, Hai-Gang (Frontiers in Pharmacology, 2016)
The forkhead/winged helix transcription factor (Fox) p3 can regulate the expression of various genes, and it has been reported that the transfer of Foxp3-positive T cells could ameliorate cardiac hypertrophy and fibrosis. Triptolide (TP) can elevate the expression of Foxp3, but its effects on cardiac hypertrophy remain unclear. In the present study, neonatal rat ventricular myocytes (NRVM) were isolated and stimulated with angiotensin II (1 μmol/L) to induce hypertrophic response. The expression of Foxp3 in NRVM was observed by using immunofluorescence assay. Fifty mice were randomly divided into five groups and received vehicle (control), isoproterenol (Iso, 5 mg/kg, s.c.), one of three doses of TP (10, 30, or 90μg/kg, i.p.) for 14 days, respectively. The pathological morphology changes were observed after Hematoxylin and eosin, lectin and Masson's trichrome staining. The levels of serum brain natriuretic peptide (BNP) and troponin I were determined by enzyme-linked immunosorbent assay and chemiluminescence, respectively. The mRNA and protein expressions of α- myosin heavy chain (MHC), β-MHC and Foxp3 were determined using real-time PCR and immunohistochemistry, respectively. It was shown that TP (1, 3, 10 μg/L) treatment significantly decreased cell size, mRNA and protein expression of β-MHC, and upregulated Foxp3 expression in NRVM. TP also decreased heart weight index, left ventricular weight index and, improved myocardial injury and fibrosis; and decreased the cross-scetional area of the myocardium, serum cardiac troponin and BNP. Additionally, TP markedly reduced the mRNA and protein expression of myocardial β-MHC and elevated the mRNA and protein expression of α-MHC and Foxp3 in a dose-dependent manner. In conclusion, triptolide can effectively ameliorate myocardial damage and inhibit cardiac hypertrophy, which is at least partly related to the elevation of Foxp3 expression in cardiomyocytes.